The Effect Of Liquidity On The Profitability Of Commercial Banks In Indonesia During The Post-COVID-19 Pandemic Recovery Period (2021–2024) - Olivia Dhesta Vega; Marshella Zuliani; Tessa Meilandari; Reva Indah Sefira (Jurnal Akuntansi, Manajemen dan Bisnis Digital, 2026)
The purpose of this research is to analyze the relationship between liquidity and the profitability of Indonesian commercial banks from 2021 to 2024. The Loan to Deposit Ratio (LDR) is a liquidity metric, whereas the RO) is a measure of profitability. The commercial banks that were active in Indonesia over the time frame of this study make up the population. With the use of purposive sampling, a total of fifteen banks were examined, yielding sixty observations. Secondary data culled from Financial Services Authority annual reports served as the basis for this study. We used Microsoft Excel to process the data.Simple linear regression analysis is the analytical approach used in this investigation. There was no statistically significant relationship between ROA and the Loan to Deposit Ratio (LDR), according to the findings. According to the coefficient of determination, other factors account for 99.2% of the variation in ROA, whereas LDR only accounts for 0.8%. These results indicate that during the economic recovery phase following a pandemic, liquidity is not the main factor that determines a bank's profitability.